A method and device for preparing a solar thermal conversion film.
By introducing a MoS2/Fe3O4 nanorod array film with a temperature differential power generation sheet and a core-shell structure into the solar interface evaporator, the problems of heat exchange loss and salt scale formation during the photo-heat conversion are solved, and efficient thermal energy reuse and power generation effects are achieved.
Patent Information
- Application Number
- CN202411888539.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing solar interface evaporators have heat exchange losses during the photothermal conversion process, resulting in a decrease in energy utilization, a slowdown in steam condensation rate, and a high interface temperature leads to the formation of salt scale, affecting equipment efficiency.
A photothermal conversion film that uses temperature difference power generation is designed. By adding a temperature difference power generation sheet below the evaporator interface, the lost latent heat is converted into electrical energy, and a core-shell structure MoS2/Fe3O4 nanorod array film is used as a high-efficiency photothermal conversion material to improve thermal evaporation efficiency.
Effective reuse of lost thermal energy is achieved, evaporation rate and power generation is improved, salt scale formation is reduced, and the overall efficiency of the equipment is improved.
Smart Images

Figure CN119750655A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterial preparation, and in particular to a method and device for preparing a photothermal conversion film using solar energy. Background Art
[0002] With the continuous growth of the global population and the acceleration of industrialization, the demand for water resources and energy continues to increase. This not only poses a challenge to the sustainable development of human society, but also puts pressure on the environment and ecosystems. Solar energy and seawater are the two most abundant resources on the earth. The use of solar thermal desalination has the advantages of independent operation and is not restricted by conditions such as electricity. It is considered to be a promising green energy utilization strategy. From the perspective of solar interface evaporation device design, the development of new photothermal materials is key. However, due to the continuous input of solar energy, the temperature of the photothermal conversion interface is always higher than the ambient temperature, and there is inevitably heat exchange loss to the environment, resulting in a decrease in the utilization rate of solar energy. Therefore, the evaporation rate of the current solar energy interface evaporator is often lower than the theoretical value of 1.47 kg m -2 h -1 More importantly, this heat diffusion can raise the ambient temperature, reducing the steam condensation rate, creating a vicious cycle. Furthermore, high temperatures at the evaporator interface not only reduce evaporation efficiency but also form a high salt concentration region below the interface, causing salt scaling. Therefore, reusing the latent heat energy lost from this ambient heat has become a key focus for future development. Summary of the Invention
[0003] To fully utilize the heat energy lost to the environment during the photothermal conversion process, this invention utilizes the temperature difference between the evaporator interface and the ambient temperature to generate thermoelectric power, converting the lost heat energy into electricity. This solves both the heat energy reuse issues of traditional evaporators and the steam condensation rate issues associated with high interface temperatures. It also maintains continuous power generation due to the temperature difference, effectively integrating multiple benefits.
[0004] The designed solar water vapor-electricity cogeneration evaporator is shown in the abstract. Key components of this evaporator include a high-efficiency photothermal conversion membrane and a thermoelectric generator, which utilizes heat loss for thermoelectric power generation. Specifically, a thermoelectric generator is incorporated below the evaporation interface to convert lost latent heat into electricity. To increase the temperature of the high-temperature layer, a core-shell MoS2 / Fe3O4 nanorod array thin film was synthesized as a highly efficient photothermal conversion material. This thin film is tightly bonded to a water-absorbing plant fiber filter paper, forming a component of the thermoelectric high-temperature layer. The highly photothermal-converting MoS2 / Fe3O4 membrane is composed of a directional arrangement of spindle-shaped core-shell nanorods, forming a highly efficient photothermal conversion layer with rapid water transport channels. This enables efficient thermal evaporation and provides the upper surface temperature for thermoelectric power generation. The membrane also exhibits significant salt tolerance. Power generation devices can utilize this single-layer membrane structure to generate a temperature differential with the ambient air temperature, thereby generating electricity. A double-layer membrane can also be used for power generation, where the lower surface of the power generation sheet is composed of a water-absorbing plant fiber filter paper layer, which continuously draws water at ambient temperature from the water body to reduce the low temperature, thereby increasing the temperature difference and power generation. Since the ambient temperature is continuously lower than the temperature of the photothermal conversion interface, the power generation state can be maintained continuously. Under 1 sun, the evaporation rate of the double-layer membrane structure evaporator is 1.55 kg m -2 h -1 and 1.76W m -2 of electricity.
[0005] To achieve the above objectives, the present invention provides a method and device for preparing a photothermal conversion film using solar energy, comprising:
[0006] S1, synthesizing Fe2O3 nanotubes by hydrothermal method;
[0007] S2, reducing Fe2O3 nanotubes to Fe3O4 nanorods under hydrogen atmosphere;
[0008] S3, using Fe3O4 nanorods as templates, hydrothermal method was used to uniformly grow MoS2 on the nanorods to obtain MoS2 / Fe3O4 core-shell structure nanorods;
[0009] S4. MoS2 / Fe3O4 nanorod array thin films were synthesized by hydrothermal method under the assistance of magnetic field as interfacial evaporator photothermal conversion film;
[0010] S5. The photothermal conversion film and the thermoelectric power generation sheet are assembled into a device, which can simultaneously realize the dual functions of seawater desalination and power generation.
[0011] Preferably, the step uses Fe3O4 nanorods as templates, and uniformly grows MoS2 on the nanorods by a hydrothermal method to obtain MoS2 / Fe3O4 core-shell structure nanorods. The hydrothermal temperature is 180-200°C, and the reaction is carried out for 12 hours.
[0012] Preferably, in step S5, the photothermal conversion membrane and the thermoelectric power generation sheet are assembled into a device that can simultaneously realize the dual functions of seawater desalination and power generation. A double-layer membrane structure is preferably adopted, wherein the upper membrane is a MoS2 / Fe3O4 photothermal conversion membrane and a plant fiber filter paper membrane closely attached thereto. The lower layer of the thermoelectric power generation sheet is a plant fiber filter paper membrane;
[0013] Compared with the existing technology, the present invention has the following advantages: the synthesized core-shell structure photothermal conversion array membrane has high photothermal conversion performance. The designed device integrates seawater desalination and power generation, which can simultaneously produce fresh water and generate electricity. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a SEM image of the Fe2O3 nanotubes prepared in Example 1 of a method for preparing a photothermal conversion film using solar energy and a device according to the present invention;
[0015] Figure 2 This is a SEM image of Fe3O4 nanorods prepared in Example 1 of a method for preparing a photothermal conversion film using solar energy and a device according to the present invention;
[0016] Figure 3 This is an SEM image of MoS2 / Fe3O4 core-shell structure nanorods in Example 1 of a method for preparing a photothermal conversion film using solar energy and a device according to the present invention;
[0017] Figure 4 TEM image of MoS2 / Fe3O4 core-shell structure nanorods in Example 1 of a method for preparing a photothermal conversion film using solar energy and a device according to the present invention;
[0018] Figure 5 This is a high-resolution MoS2 TEM image of MoS2 / Fe3O4 core-shell structured nanorods in Example 1 of a method for preparing a photothermal conversion film using solar energy and a device according to the present invention;
[0019] Figure 6 This is the preparation process of the MoS2 / Fe3O4 array photothermal conversion film in Example 1 of a photothermal conversion film preparation method and device utilizing solar energy according to the present invention;
[0020] Figure 7 Schematic diagram of a solar energy desalination and power generation integrated device in Example 1 of a method for preparing a photothermal conversion film and device utilizing solar energy according to the present invention;
[0021] Figure 8 Temperature distribution diagrams on the surface and side of the MoS2 / Fe3O4 array photothermal conversion film in Example 1 of a method for preparing a photothermal conversion film and device utilizing solar energy according to the present invention;
[0022] Figure 9 This is a comparison chart of the power generation voltage of the evaporator designed with a single-layer film structure and a double-layer film structure in Example 2 of a method for preparing a photothermal conversion film using solar energy and a device according to the present invention;
[0023] Figure 10 This is a test of the surface hydrophilicity of the MoS2 / Fe3O4 array photothermal conversion film in Example 4 of a method for preparing a photothermal conversion film and a device using solar energy according to the present invention;
[0024] Figure 11 This is a test diagram of the salt adsorption resistance of the MoS2 / Fe3O4 array photothermal conversion film surface in Example 4 of a method for preparing a photothermal conversion film and device using solar energy according to the present invention; DETAILED DESCRIPTION
[0025] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0026] Example 1
[0027] A method and device for preparing a photothermal conversion film using solar energy, wherein the synthesized photothermal conversion film comprises the following steps:
[0028] S1. Synthesize Fe2O3 nanotubes using a hydrothermal method: Dissolve 1.35g of FeCl3·6H2O in 200mL of deionized water. Dissolve 0.0144g of NH4H2PO4 in 20mL of deionized water. Then mix the two solutions and stir them magnetically for 10 minutes. Transfer them to a 100mL stainless steel reactor and react at 200℃ for 16 hours. Wash the resulting product several times with deionized water and ethanol, and then centrifuge and dry to obtain Fe2O3 nanotubes. The synthesized Fe2O3 nanotubes (attached) Figure 1 ), outer diameter is 120-300nm, tube thickness is 20-30nm, and length is 400-1000nm.
[0029] S2. Under hydrogen atmosphere, Fe2O3 nanotubes were reduced to Fe3O4 nanorods: an appropriate amount of Fe2O3 nanotube sample was placed in a tube furnace and reacted in a mixture of hydrogen and argon at 450°C for two hours. After cooling to room temperature, the sample was removed to obtain Fe3O4 nanorods. Fe3O4 exhibited a spindle-shaped rod structure (see attached). Figure 2 ), the diameter of the rods is 150-400nm and the length is 600-1200nm.
[0030] S3. Using Fe3O4 nanorods as templates, MoS2 was uniformly grown on the nanorods by hydrothermal method to obtain MoS2 / Fe3O4 core-shell structure nanorods: 0.1g Fe3O4 nanorods were dispersed in 50mL deionized water and ultrasonicated to obtain solution A. Subsequently, 0.5g (NH4)6Mo7O 24 4H2O and 1g thiourea were dissolved in 50mL of deionized water to obtain solution B. After stirring and ultrasonic treatment, solution A (40mL) and solution B (40mL) were mixed and transferred to a 100mL stainless steel reactor. The mixture was heated at 180°C for 12 hours. The resulting product was centrifuged, washed, and then dried in an oven to obtain the SEM image of MoS2 / Fe3O4 core-shell nanorods. Figure 3 The morphology is spindle-shaped nanorods, and the surface is covered with MoS2 nanorods. Figure 4 This is the TEM image of the synthesized MoS2 / Fe3O4 nanorods, with Fe3O4 inside and MoS2 nanosheets on the surface. The interlayer spacing of MoS2 is 0.65nm, corresponding to the 2H phase of the (002) lattice plane, see Appendix Figure 5 shown.
[0031] S4. Under the assistance of magnetic field, MoS2 / Fe3O4 nanorod array thin film was synthesized by hydrothermal method as the interface evaporator photothermal conversion film. The preparation process is shown in the attached schematic diagram. Figure 6 , utilizing the magnetic properties of Fe3O4 in MoS2 / Fe3O4 powder, under the action of an external magnetic field, MoS2 / Fe3O4 nanorods form an array arrangement.
[0032] S5. The light-heat conversion film and the thermoelectric power generation sheet are assembled into a device, which can simultaneously realize the dual functions of seawater desalination and power generation. The double-layer structure design is adopted. The assembled device is shown in the attached Figure 7 The surface temperature of the MoS2 / Fe3O4 array photothermal conversion film under one sun is 46.6°C, and the temperature of the plant fiber filter paper layer at the bottom of the thermoelectric generator is 36.5°C (see Appendix Figure 8 The evaporation rate of this double-layer evaporator under one sun intensity is 1.55kgm -2 h -1 , and 1.76W m -2 of electricity.
[0033] Example 2
[0034] Steps S1 to S4 are the same as steps S1 to S4 in Example 1.
[0035] S5 adopts a single-layer structure design, Figure 7The plant fiber filter paper in the middle and lower layers was removed, while the rest of the design remained the same. A comparison of the power generation voltage of this MoS2 / Fe3O4 array photothermal conversion membrane under single-sun irradiation and the power generation voltage of the evaporator with a double-layer membrane structure in Example 1 is shown in Figure 9. The power generation voltage of the double-layer evaporator increased by 31.56 mV compared to the single-layer evaporator.
[0036] Example 3
[0037] Steps S1 to S2 are the same as steps S1 to S2 in Example 1.
[0038] S3. Using Fe3O4 nanorods as templates, MoS2 was uniformly grown on the nanorods by hydrothermal method to obtain MoS2 / Fe3O4 core-shell structure nanorods: 0.1g Fe3O4 nanorods were dispersed in 50mL deionized water and ultrasonicated to obtain solution A. Subsequently, 0.5g (NH4)6Mo7O 24 4H2O and 1 g of thiourea were dissolved in 50 mL of deionized water to obtain solution B. After stirring and ultrasonic treatment, solution A (40 mL) and solution B (40 mL) were mixed and transferred to a 100 mL stainless steel reactor and reacted at 160°C for 12 hours.
[0039] S4 and S5 are the same as those in Example 1. The evaporation rate of this MoS2 / Fe3O4 array photothermal conversion film under one sun is 1.45 kg / m -2 h -1 and 1.53W m -2 of electricity.
[0040] Example 4
[0041] Steps S1 to S2 are the same as steps S1 to S2 in Example 1.
[0042] S3. Using Fe3O4 nanorods as templates, MoS2 was uniformly grown on the nanorods by hydrothermal method to obtain MoS2 / Fe3O4 core-shell structure nanorods: 0.1g Fe3O4 nanorods were dispersed in 50mL deionized water and ultrasonicated to obtain solution A. Subsequently, 0.5g (NH4)6Mo7O 24 4H2O and 1 g of thiourea were dissolved in 50 mL of deionized water to obtain solution B. After stirring and ultrasonic treatment, solution A (40 mL) and solution B (40 mL) were mixed and transferred to a 100 mL stainless steel reactor. The reaction was carried out at 220°C for 12 hours.
[0043] S4 and S5 are the same as in Example 1. This MoS2 / Fe3O4 array photothermal conversion film has good hydrophilicity, see attached Figure 10After 30 seconds, the water droplets on the surface of the light-heat conversion film completely diffused into the interior of the film. Under one sun, the evaporation rate was 1.31 kg / m -2 h -1 and 1.39W m -2 The salt deposition performance was tested in a NaCl solution (3.5 wt.%). After evaporation in a drying oven at 50°C for 8 hours, the salt deposition on the sample surface was recorded with a camera. Figure 11 As shown, the MoS2 / Fe3O4 array photothermal conversion film shows obvious resistance to salt deposition, which is better than the blank filter paper film, MoS2 and Fe3O4 films.
[0044] Example 5
[0045] S1. Synthesis of Fe2O3 nanotubes using a hydrothermal method: Dissolve 1.35g of FeCl3·6H2O in 200mL of deionized water. Dissolve 0.04g of NH4H2PO4 in 20mL of deionized water. Combine the two solutions and stir magnetically for 10 minutes. Transfer the mixture to a 100mL stainless steel reactor and react at 180°C for 20 hours. Wash the resulting product multiple times with deionized water and ethanol, then centrifuge and dry to obtain Fe2O3 nanotubes. The synthesized Fe2O3 nanotubes have an outer diameter of 150-200nm, a thickness of 25-35nm, and a length of 1200-2000nm.
[0046] S2. Reduction of Fe2O3 nanotubes to Fe3O4 nanorods in a hydrogen atmosphere: An appropriate amount of Fe2O3 nanotube sample was placed in a tube furnace and reacted in a mixture of hydrogen and argon at 350°C for 4 hours. After cooling to room temperature, the sample was removed to obtain Fe3O4 nanorods. The Fe3O4 nanorods exhibited spindle-shaped rods with a diameter of 300-500 nm and a length of 1200-1800 nm.
[0047] S3. Using Fe3O4 nanorods as templates, MoS2 was uniformly grown on the nanorods by hydrothermal method to obtain MoS2 / Fe3O4 core-shell structure nanorods: 0.1g Fe3O4 nanorods were dispersed in 50mL deionized water and ultrasonicated to obtain solution A. Subsequently, 0.5g (NH4)6Mo7O 24 4H2O and 1g of thiourea were dissolved in 50mL of deionized water to obtain Solution B. After stirring and sonication, Solution A (40mL) and Solution B (40mL) were mixed and transferred to a 100mL stainless steel reactor. The mixture was incubated at 150°C for 14 hours. The resulting product was centrifuged, washed, and then dried in an oven to obtain MoS2 / Fe3O4 core-shell nanorods.
[0048] S4. Under the assistance of magnetic field, MoS2 / Fe3O4 nanorod array film was synthesized by hydrothermal method as interface evaporator photothermal conversion film.
[0049] S5. The photothermal conversion film and the thermoelectric power generation sheet are assembled into a device with a double-layer structure. The surface temperature of the MoS2 / Fe3O4 array photothermal conversion film can reach a maximum of 53.6°C under one sun, and the temperature of the plant fiber filter paper layer at the bottom of the thermoelectric power generation sheet is 28.2°C. The evaporation rate of this double-layer evaporator under one sun intensity is 1.60kg / m -2 h -1 , and 1.81W m -2 of electricity.
[0050] The number of devices and processing scales described herein are intended to simplify the description of the present invention, and applications, modifications, and variations of the present invention will be apparent to those skilled in the art.
[0051] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A method and device for preparing a photothermal conversion film using solar energy, characterized in that: The following steps are involved: S1, synthesizing Fe2O3 nanotubes by hydrothermal method; S2, reducing Fe2O3 nanotubes to Fe3O4 nanorods under hydrogen atmosphere; S3, using Fe3O4 nanorods as templates, hydrothermal method was used to uniformly grow MoS2 on the nanorods to obtain MoS2 / Fe3O4 core-shell structure nanorods; S4. With the assistance of magnetic field, MoS2 / Fe3O4 nanorod array film was synthesized by hydrothermal method as interfacial evaporator photothermal conversion film. S5. The photothermal conversion film and the temperature difference power generation sheet are assembled into a device, which can realize the dual functions of seawater desalination and power generation at the same time.
2. A method and device for preparing a photothermal conversion film using solar energy as claimed in claim 1, characterized in that: The process of hydrothermal synthesis of Fe2O3 nanotubes in step S1 is as follows: a certain amount of FeCl3·6H2O is dissolved in 200 mL of deionized water to obtain solution A, and NH4H2PO4 is added and dissolved in 20 mL of deionized water to obtain solution B. Then solutions A and B are combined and magnetically stirred for 10 minutes to obtain solution C. Subsequently, 80 mL of solution C is transferred to a 100 mL stainless steel reactor for hydrothermal reaction. The obtained product is washed with deionized water and ethanol, then centrifuged and dried at 80°C to obtain Fe2O3 nanotubes.
3. The NH4H2PO4 as claimed in claim 2 is a Fe2O3 nanotube regulator, and the mass ratio of the added amount to FeCl 3·6H2O is 1%-3%.
4. The hydrothermal reaction temperature as claimed in claim 2 is 180-200° C. and the reaction time is 16-20 hours.
5. A method for preparing a photothermal conversion film using solar energy and a device as claimed in claim 1, characterized in that: In step S2, the Fe2O3 nanotubes are reduced to Fe3O4 nanorods.
6. The reducing atmosphere as claimed in claim 2 is a mixture of hydrogen and argon, and the reaction is carried out at 350-450°C for 2-4 hours.
7. A method for preparing a photothermal conversion film using solar energy and a device as claimed in claim 1, characterized in that: The method comprises taking Fe3O4 nanorods as templates, uniformly growing MoS2 on the nanorods by a hydrothermal method, obtaining MoS2 / Fe3O4 core-shell structure nanorods, and carrying out the reaction process under stirring of an external magnetic field.
8. The hydrothermal method as claimed in claim 4, wherein the temperature is 150-220°C and the reaction time is 10-14 hours.
9. A method for preparing a photothermal conversion film using solar energy and a device as claimed in claim 1, characterized in that: In step S5, the photothermal conversion film and the temperature difference power generation sheet are assembled into a device, which can simultaneously realize the dual functions of seawater desalination and power generation.
10. A method and device for preparing a photothermal conversion film using solar energy as claimed in claim 1, wherein a single-layer film structure or a double-layer film structure can be used to achieve the maximum temperature difference. A double-layer film structure is preferably used, wherein the upper film is a MoS2 / Fe3O4 photothermal conversion film and a plant fiber filter paper film closely attached thereto. The lower layer of the temperature difference power generation sheet is a plant fiber filter paper film.